2010
DOI: 10.1007/s00406-009-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced prefrontal gyrification in obsessive–compulsive disorder

Abstract: Structural magnetic resonance imaging (MRI) studies reveal evidence for brain abnormalities in obses-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…However, the full relevance also regarding the relationship with other neurobiological features and the exact pathophysiological origin of cortical folding alterations is not clear and matter of an ongoing debate [26,27,46]. Cortical folding alterations have also been found in obsessive-compulsive disorder [47,48]. Again, both hypo-and hypergyria have been identified.…”
Section: Cortical Folding and Anorexia Nervosamentioning
confidence: 97%
“…However, the full relevance also regarding the relationship with other neurobiological features and the exact pathophysiological origin of cortical folding alterations is not clear and matter of an ongoing debate [26,27,46]. Cortical folding alterations have also been found in obsessive-compulsive disorder [47,48]. Again, both hypo-and hypergyria have been identified.…”
Section: Cortical Folding and Anorexia Nervosamentioning
confidence: 97%
“…Thicker and thinner cortical regions co-exist in 22q11.2 deletion syndrome (Bearden et al 2007, 2009; Schaer et al 2009), autism spectrum disorder (Hyde et al 2010; Jiao et al 2010), and Turner syndrome (Raznahan et al 2010). Regions of higher gyrification have been reported in 22q11.2 deletion syndrome (Bearden et al 2009), autism spectrum disorder (Awate et al 2008), children born preterm (Kesler et al 2006), and Williams syndrome (Thompson et al 2005; Gaser et al 2006); regions of lower gyrification in ADHD (Wolosin et al 2009), dyslexia (Casanova et al 2004), intellectual disability (Zhang et al 2010), obsessive-compulsive disorder (Wobrock et al 2010), and Turner syndrome (Raznahan et al 2010). Regions of both higher and lower gyrification have been reported in schizophrenia (White and Hilgetag 2011), and temporal lobe epilepsy (Lin et al 2007; Voets et al 2011).…”
Section: Many Childhood Disorders Involve Plasticity-homeostasis Dmentioning
confidence: 99%
“…Very recently, Nakame et al have reported significantly reduced cortical thickness I the left superior temporal gyrus and posterior insular cortex in OCD patients; in addition, there was a significant negative correlation between cortical thickness in the left postcentral and right superior parietal gyri and "cleaning" dimension scores (Nakamae et al, 2012). Till date, the only study examining cortical folding pattern in medicated OCD patients has revealed prefrontal hypogyrification (Wobrock et al, 2010). Cortical surface area profile in OCD is yet to be explored.…”
Section: Introductionmentioning
confidence: 97%